THE SETTING MECHANISM OF MINERAL TRIOXIDE AGGREGATE - Halenur Altan; Gül Tosun (Istanbul University, 2016)
Mineral trioxide aggregate (MTA) is a powder containing calcium silicate composed of hydrophilic particles which harden at the presence of moisture. MTA was initially introduced as a root end filling material. Due its practical advantages that include superior biocompatility, effective sealing capability, and the ability to improve regeneration of the pulp and peripheral root tissues, it is used in different clinical applications such as pulp capping, apexification, pulpotomy and perforation. Despite being a promising material in endodontic treatment, MTA is not commonly used. Long setting time is the main clinical disadvantage of MTA. The aim of this review is to provide an overview of the current literature concerning the setting mechanism of MTA, accelerators and devices used to evaluate various steps of the hardening process.